Adding value to Africa's cassava in a global environment - Adebayo, K.; Abayomi, L.; Alacho, O.F.; Dziedzoave, N.T.; Forsythe, L.; Graffham, A.J.; Ilona, Paul; Kleih, Uli K.; Lamboll, R.I.; Mahende, G.; Martin, A.M.; Onumah, G.E.; et al. (International Association of Hydrological Sciences, 2012)
Based on experiences in the Cassava: Adding Value for Africa (C:AVA) project, this paper examines emerging issues and lessons for adding value to cassava, one of Africa's widely cultivated staples in ways that contribute to the global market environment as well as bring benefits to small holders on the continent. The main issues discussed include: competiveness in the supply of raw material, assisting smallholders to produce value-added products sustainably and competitively, ensuring and maintaining quality of products, selecting appropriate technologies for different circumstances and anticipating negative effects of the market environment on smallholders. One of the main challenges for value addition to a staple crop in Africa is finding 'champions' who are willing to make new investments with knowledge, skill and expertise requirements derived from other nations. The other is increasing the drying capacities for a tropical root crop through appropriate technologies that ensure production of high quality products in required volumes. One focus of the C:AVA project in the near future is to promote transfer of energy efficient Nigerian-made flash drier in collaboration with partners and fabricators from other C:AVA countries (Ghana, Uganda, Malawi and Tanzania). Improved energy efficiency will reduce fuel consumption, reduce operating cost and improve throughput of the dryers. An additional benefit will be reduction in emission of harmful greenhouse gases and their impact on global warming. It is anticipated that the knowledge and skills for further developing the value addition potential for cassava in all five countries will be enhanced. Benchmarking of key variables was used as an approach to understand differences between countries in terms of their abilities to develop high quality cassava flour value chains. It is clear that one strategy does not work in all countries and while positive government support for cassava development is helpful, the real driver is targeting markets according to realisable capacities of the smallholder actors in the value chain.